Association of Exon 14 of the SOX6 Gene Sequence Variations with Response to Hydroxyurea Therapy in Patients Carrying Non Transfusion-Dependent Thalassemia. (1st November 2020) - Mohammadi, Zahra; Mohammadi, Reza; Haghpanah, Sezaneh; Moghadam, Mohamad; Pazhoomand, Reza; Karimi, Mehran
Abstract: Hydroxyurea (HU) activates the γ-globin gene, resulting in increased Hb F synthesis. The SOX6 gene is a member of the Sox (Sry-type HMG box) family of transcription factors, characterized by minor groove binding domain. The DNA binding domain of this gene is encoded by exon 14. We assessed the relationship between response to HU and exon 14 of the SOX6 gene sequence variations in patients with non transfusion-dependent thalassemia (NTDT). One hundred NTDT patients from southern Iran underwent HU therapy randomly participated in this cross-sectional study between February 2013 and October 2014. Based on response to HU therapy, the patients were divided into two groups: good and poor responder. Sequence variations of exon 14 of the SOX6 gene was assayed by the Sanger sequencing technique. From all evaluated single nucleotide polymorphisms (SNPs) as above, we found no significant association between sequence variations of exon 14 of the SOX6 gene and response to HU therapy ( p  > 0.05). It seems that no SNPs in exon 14 of the SOX6 gene is associated with response to HU in NTDT patients, but more studies are needed for further evaluation.